PRIORITY DETERMINATION FOR THE DEVELOPMENT OF THE WEST SUMATRA CREATIVE ECONOMY SUBSECTOR - Ansofino, Ansofino; Sari, Putri Meliza; Rosya, Nilmadesri; Yulio, Anggri; Rezki, Afrital (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2023)
The focus of this research is how to rank the West Sumatra creative economy sub-sector using creative economy indicators according to law No. 24 of 2019, Added Value, Intellectual Property, Cultural Heritage and Science and Technology. The research was conducted in six sub-sectors with the largest proportion of creative entrepreneurs in 2022. This study used the promethee ranking method, and GAIA analysis. The results of the study show that the competitiveness of the West Sumatra creative economy sub-sector is determined by cultural heritage and use of technology as well as the role of the workforce and developing the creative economy. There are three sub-sectors that have advantages based on creative economic indicators in West Sumatra, namely the Fashion, Performing Arts and Design sub-sectors. The factors causing its superiority are mainly in terms of cultural inheritance and the application of technology in the products created. The design policy for increasing the competitiveness of the West Sumatra creative economy sub-sector can be carried out most urgently (necessary conditions), increasing awareness of creative business actors registering intellectual property rights for creative products.